Message from the Program Chairs - Boeres, Cristina; Prasanna, Viktor K. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2022)
Presents the conference keynote speech, plenary speech, or messages from conference chairs.